The Reform of Old Slavonic in Preslav School of Simeon - Хабургаев, Г. А. (Kalbotyra, 1988)
The article deals with the history of Cyrillic alphabet foundation in East Bulgaria under Simeon (893–927). The creation of a new Old Slavonic alphabet in which some letters from the Glagolitic alphabet were introduced to express the Slavonic phonemes missing in the Greek language is treated by the author as the reform of the Old Slavonic. This reform is regarded as the first attempt to apply an Old Slavonic norm to the native language of the Old Slavonic writers.